Long-term seed burial reveals differences in the seed-banking strategies of naturalized and invasive alien herbs - Moravcová, Lenka; Carta, Angelino; Pyšek, Petr; Skálová, Hana; Gioria, Margherita (Scientific reports, 2022)
Soil seed viability and germinability dynamics can have a major influence on the establishment and spread of plants introduced beyond their native distribution range. Yet, we lack information on how temporal variability in these traits could affect the invasion process. To address this issue, we conducted an 8-year seed burial experiment examining seed viability and germinability dynamics for 21 invasive and 38 naturalized herbs in the Czech Republic. Seeds of most naturalized and invasive species persisted in the soil for several years. However, naturalized herbs exhibited greater seed longevity, on average, than invasive ones. Phylogenetic logistic models showed that seed viability (but not germinability) dynamics were significantly related to the invasion status of the study species. Seed viability declined earlier and more sharply in invasive species, and the probability of finding viable seeds of invasive species by the end of the experiment was low. Our findings suggest that invasive herbs might take advantage of high seed viability in the years immediately after dispersal, while naturalized species benefit from extended seed viability over time. These differences, however, are not sufficiently strong to explain the invasiveness of the species examined.
Keywords: zavlečené druhy; Seeds; půda; Soil; semenná banka; Introduced Species; Phylogeny; Seed Bank; fylogeneze; semena rostlinná